Evaluasi Kapasitas Tiang Pancang Miring pada Pilar Jembatan Tipe Pile Cap - Rosyada, Ananda Sabiila; Indianto, Andi (Indonesian Society of Applied Science, 2021)
In the implementation of the construction of the Main Bridge on the X Toll Road project, there was a change in the shape of the structure in the form of a slope of the P2 pile that did not match the DED by 3°. So that with the change in the shape of the structure, it is necessary to evaluate the capacity of the P2 pile and the influence on other structures must be considered. This research discusses how the capacity of the pile after experiencing a slope and how to handle it properly if the pile capacity is inadequate. Pile capacity evaluation is done by checking the dimensional capacity, reinforcement capacity, foundation bearing capacity, and deflection of the P1-P2 superstructure using the help of software SAP2000 in analyzing. The results showed that the pile capacity at P2 was inadequate, indicated by the lack of reinforcement on the piles as much as 6-D10,7 mm and column P2 as much as 9-D10,7 mm. As a result of inadequate pile capacity, the P1-P2 connection lacks top reinforcement. Therefore, structural strengthening is needed to make the P1-P2 structure more rigid by making bracing concrete with a length of 18,78 meters, a width of 33,92 meters, and a thickness of 0,8 meters with the need for longitudinal reinforcement and transverse reinforcement D32-250. After the structural strengthening is done, the required area of reinforcement for columns P2, piles P2, and connections P1-P2 are all fulfilled with those already installed in the side.